Pertanggunghawaban Pidana Pelaku Cyber Crime Terhadap Pengedaran Foto Bermuatan Pornografi Di Media Sosial (Studi Ditressiber Polda jatim) - Ahmad Mu’Affan Alaufan; M. Syahrul Borman; Nur Handayati (CV. Ulil Albab Corp, 2026)
The development of information technology has transformed conventional crimes into more sophisticated forms of cybercrime, creating new challenges in law enforcement. One of the emerging issues is the circulation of pornographic images through social media platforms. Therefore, professionalism and expertise of law enforcement officers, particularly investigators from the Indonesian National Police, are required to effectively handle such cases. This research aims to analyze the legal regulation of criminal sanctions against cybercrime involving the distribution of pornographic images on social media and to determine the elements of fault and criminal sanctions as the basis for criminal liability. The study employs a normative juridical research method, focusing on the analysis of statutory regulations, legal principles, court decisions, and legal doctrines related to cybercrime and pornography offenses. The results show that although Indonesia guarantees freedom in accessing information and technology, the state also imposes legal restrictions on activities conducted in cyberspace to prevent criminal acts. The distribution of pornographic content through social media constitutes a violation of decency norms and is subject to criminal sanctions under several legal instruments, particularly the Law on Information and Electronic Transactions (ITE Law) and the Pornography Law. Criminal liability can be imposed when the elements of unlawful acts, fault, and the capability of the offender to be held responsible are fulfilled. Thus, law enforcement against cybercrime involving pornographic content requires strict application of legal provisions to ensure legal certainty, protect public morality, and maintain social order.